Angiographic assessment of the efficacy of flow diverter treatment for cerebral aneurysms - Sadasivan, Chander; Dholakia, Ronak; Peeling, Lissa; Gölitz, Philipp; Dörfler, Arnd; Lieber, Baruch B.; Fiorella, David J.; Woo, Henry H. (Interventional Neuroradiology, 2019)
Background: The recent growth of neuro-endovascular treatment has rekindled interest in the use of angiographic techniques for flow assessment. Aneurysm treatment with flow diverters is particularly amenable to such analysis. We analyze contrast time–density curves — recorded within aneurysms before (pre) and immediately after (post) flow diverter implantation to estimate six-month treatment outcomes. Methods: Fifty-six patients with 65 aneurysms were treated with flow diverters at two institutions. A region of interest was drawn around the aneurysm perimeter in image sequences taken both pre and post angiography, and the temporal variation in grayscale intensity within the aneurysm (time–density curve) was recorded. Eleven parameters were quantified from each time–density curve. Aneurysm occlusion status was recorded six months post treatment. The change in parameters from pre to post treatment was statistically evaluated between aneurysm occluded and non-occluded groups. Results: Of the 11 parameters, eight were significantly different before and immediately after flow diversion. Considering the entire data set, none of the parameters was statistically different between the occluded and non-occluded groups. However, subgroup analyses showed that four variables were significantly different between the aneurysm occluded and non-occluded groups. The sensitivity of these variables to predict aneurysm occlusion at six months ranged from 60% to 89%, while the specificity ranged from 55% to 70%. Conclusions: Device-induced intra-aneurysmal flow alterations quantified by simple aneurysmal time–density curves can potentially be used to predict long-term outcomes of flow diversion. Large multi-center studies will be required to confirm these findings. Patient-to-patient variability in coagulation may need to be incorporated for clinically relevant predictive values.
CRIS-Team Scopus Importer:2019-07-23
Keywords: Concentration–time curve; contrast washout; time–density curve